A preliminary study on the malay online newspaper's coverage towards local food business / Siti Hajar Abd Aziz ... [et al.] - Abd Aziz, Siti Hajar; Mohd Azni, Zuliani; Khamis, Muhamad Hanapi; Mohamad Jaini, Siti Nur Nadhirah (2021)
Business enterprises in Malaysia are classified as small and medium enterprises when meeting either one of the two criteria, the number of full-time employees and value of the enterprise annual sales turnover. Small and Medium Food Enterprises (SMFE), of the most popular SME in Malaysia, makes up more than 80 percent of the total number of establishments in this sector, and are mainly involved in producing processed livestock products, processed fisheries products, processed fruits, processed vegetables, cocoa products, and cereals. The study aims at understanding the role of online Malay newspapers in their coverage on the development and growth of the SMFEs. Using purposive sampling, 20 news articles from three Malay newspapers, namely the Berita Harian, Utusan Malaysia and Kosmo!, were gathered from local sections to analyse its role and coverage. The study found that although the depth of the media coverage on SMFEs may not be extensive enough, they are still favourable, showing positive tones in the reporting and indicating signs of good support for the food industry from the media. This preliminary finding serves as a foundation to more in-depth studies to have a better understanding of the content of the online news on Malaysian business, particularly the SMFEs